Densities and Excess Volumes for PEG 200 and PEG 400 with Nitrobenzene at Different Temperatures - N. Vora, Dinesh; Dodwad, S.S. (Asian Journal of Chemistry, 2010)
Densities, excess volumes for PEG 200 + nitrobenzene and PEG 400 + nitrobenzene at three different temperatures have been studied. Excess volumes (VE) are calculated over entire range of compositions at three different temperatures using the standard equation. The data are fitted in to empirical equation VE/X1X2 = [a + b(2X1 – 1) + c(2X1 – 1)2] and constants are evaluated by the least squares method along with standard deviation σ. The marked reduction in VE with increase in C—C chain length of PEG solvents is discussed in the light of hydrogen bonding.